The Cham Muslims of Cambodia: From Forgotten Minority to Focal Point of Islamic Internationalism (American Journal of Islam and Society, 2006)
The Cham Muslims of Cambodia are descendents of Champa, a once-powerful Hindu-Buddhist kingdom located in modern-day central and southern Vietnam. Champa existed from the second century CE until its complete annexation by its long-time rival, the Dai Viet, in 1832.1 Its gradual loss of territory caused several waves of immigration to Cambodia between the crucial dates of 1471 and 1835 (the start of violent repression against the Cham in their last, and finally also annexed, principality: Panduranga).2 It seems that the first wave allied itself with Cambodia’s Malay community, with whom the Cham share ethno-linguistic (as both groups are speakers of Austronesian languages) and cultural (e.g., matrilinear customs) heritage, as well as their status as foreign immigrants. Through this contact, they were Islamized. This article presents an overview of the religious and political development of Cambodia’s Cham Muslims, most of whom are Sunnis, from the days of French colonialism up to the present, and shows how this formerly neglected minority became a showcase of Islamic internationalism. Contact persons or interviewees were recommended to me by Dr. Sos Mousine (CMDF, CAMSA, and the Ministry of Agriculture), Set Muhammadsis (CAMSA, CMDF) or Dato Hajji Alwi Muhammad (MAI Terengganu), or were sought out by myself. As I was mainly interested in religious change and the rebuilding of religious infrastructure, I visited many mosques and schools for interviews, which were conducted in English, Arabic, or with a Khmer or Cham translator.